Determinants of customers’ loyalty for hospitality industry - Akbar, Sher (Information Management and Business Review, 2011)
Customer loyalty is very necessary for the competitive market environment. The growing presence of relationship marketing efforts has led to increased competition among service providers. So hospitality industry is more service oriented, effecting by customers’ interest. To achieve the desirable customer to the business, for this purpose Relationship marketing efforts would have to be implemented in order to determine whether frequent guest is loyal to the particular company. Previous research has identified the determinants of customers’ loyalty for a hotel industry and has been adapted and used in this study. Structural equation analysis was applied to identify which factors (service quality, customer satisfaction, trust, value and hotel membership program, socio demography of the customer) have positively impact customer loyalty. According the result of this study all the determinants of loyalty have significance relationship with customer loyalty, and it was also indentified that customer loyalty as a function of both behavioral and attitudinal loyalty. The framework adopted and modified for this research demonstrated the formation of a solid structure that would allow for collecting valuable findings. This study has extended and adopts the previous loyalty model and has been applied in the hotel industry of Penang, Malaysia.